2019
DOI: 10.4102/sajhivmed.v20i1.949
|View full text |Cite
|
Sign up to set email alerts
|

Switching at Low HIV-1 RNA into Fixed Dose Combinations: TDF/FTC/RPV is non-inferior to TDF/FTC/EFV in first-line suppressed patients living with HIV

Abstract: Background In low- and middle-income countries (LMICs), a substantial unmet need for affordable single-tablet regimen (STR) options remains. Rilpivirine (RPV, TMC278) is formulated in a low-cost STR with tenofovir disoproxil fumarate (TDF) and emtricitabine (FTC). Objectives Switching at Low HIV-1 RNA into Fixed Dose Combinations (SALIF) compared RPV with efavirenz (EFV), both as STRs with TDF and FTC, in maintaining virologic suppression. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Additionally, compared to baseline, there was a 15 mL/min/1.73m 3 reduction in eGFR observed at 3-months of therapy, consistent with findings from Japan that suggest a rapid decline in eGFR with TDF exposure [26]. There was also an increase in CD4+ count by 86 cells/L observed at three months of TDF therapy, consistent with the CD4+ immune cell improvement often seen in TDF-based therapy [44,45].…”
Section: Discussionsupporting
confidence: 84%
“…Additionally, compared to baseline, there was a 15 mL/min/1.73m 3 reduction in eGFR observed at 3-months of therapy, consistent with findings from Japan that suggest a rapid decline in eGFR with TDF exposure [26]. There was also an increase in CD4+ count by 86 cells/L observed at three months of TDF therapy, consistent with the CD4+ immune cell improvement often seen in TDF-based therapy [44,45].…”
Section: Discussionsupporting
confidence: 84%
“…Any disagreements were resolved by consensus. Eighteen articles met the inclusion criteria and were included in the systematic review [3][4][5][6][7][8][9][10][11][12][13][14]28,[32][33][34][35][36] (Table 1). Four of these articles were presented in tables and were not included in the quantitative metaanalyses of the efficacy and safety outcomes.…”
Section: Study Selection Data Extraction and Risk Of Bias Assessmentmentioning
confidence: 99%
“…Rilpivirine (RPV; TMC278; Edurant®) is a secondgeneration non-nucleoside reverse-transcriptase inhibitor (NNRTI) with activity against many viral strains resistant to previous NNRTIs and a moderatehigh genetic barrier to resistance development [1,2]. RPV efficacy and safety have been assessed in registrative randomized controlled clinical trials (RCTs) in HIV-positive treatment-naïve [3][4][5][6][7] and treatmentexperienced patients [8][9][10][11][12][13][14] with documented longterm efficacy and tolerability. Real-life data from observational studies [15][16][17][18][19][20][21] eventually confirmed these results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2,3 Others clinical trials have shown that the rilpivirine/emtricitabine/TDF combination can maintain virological suppression in antiretroviral (ARV)-experienced virologically-controlled PLHIV. [4][5][6][7][8] In recent trials, the dual therapy dolutegravir/rilpivirine was non-inferior to a current triple antiretroviral therapy (ART) regimen in ARV-experienced virologically-controlled PLHIV at week 48 and efficacy and safety were maintained at week 100. 9,10 It is important to obtain data from real-life settings to assess how rilpivirine is used in routine care and evaluate its virological efficacy, as a complement to data from clinical trials.…”
Section: Introductionmentioning
confidence: 99%